Employing IT Service Management to Accelerate Digital Government Transformation in Saudi Arabia: A Vision 2030 Perspective - Abudaqqa, Fatma (European Scientific Journal, ESJ, 2025)
Saudi Arabia’s Vision 2030 has placed digital transformation at the center of its government modernization agenda, with information technology positioned as a vital enabler of efficient and citizen-focused services. The objective of this study is to examine the role of IT Service Management (ITSM) in supporting this transformation, identifying both the progress achieved and the challenges that remain. A mixed-methods approach was adopted, including a survey of 80 government IT managers, interviews with key stakeholders, and a case study of a digital service platform. Findings indicate that while several public agencies have successfully implemented ITSM practices, contributing to enhanced service availability and improved citizen satisfaction, challenges persist in the form of skill shortages, outdated systems, and organizational resistance to change. Successful experiences, such as the Absher platform, underscore the importance of leadership commitment, staff training, and alignment with national objectives. Although this study demonstrates that ITSM has emerged as a critical enabler of the Kingdom’s digital government initiatives, it also highlights the need for sustained investment in leadership development, capacity building, and change management to ensure the full realization of Vision 2030 goals. As Saudi Arabia embarks on this complex and multifaceted journey, the findings suggest that continuous monitoring, institutional learning, and adaptive strategies will be essential to consolidating the benefits of ITSM within the broader framework of national transformation.